Critical infrastructure comes under attack. Issue 11 (November 2017) - Unknown
Abstract : The US Department of Homeland Security (DHS) and the Federal Bureau of Investigation (FBI) have issued a joint Technical Alert (TA17 – 293A) via US-CERT about advanced persistent threats targeting the country's energy companies and other critical infrastructure.